Tracing the evolution of dust-obscured activity using sub-millimetre galaxy populations from STUDIES and AS2UDS. Issue 1 (24th October 2020) - Dudzevičiūtė, U; Smail, Ian; Swinbank, A M; Lim, C-F; Wang, W-H; Simpson, J M; Ao, Y; Chapman, S C; Chen, C-C; Clements, D; Dannerbauer, H; Ho, L C; et al.
ABSTRACT: We analyse the physical properties of 121 SNR ≥ 5 sub-millimetre galaxies (SMGs) from the STUDIES 450 μ m survey. We model their UV-to-radio spectral energy distributions using magphys +photo- z and compare the results to similar modelling of 850 μ m-selected SMG sample from AS2UDS, to understand the fundamental physical differences between the two populations at the observed depths. The redshift distribution of the 450- μ m sample has a median of z = 1.85 ± 0.12 and can be described by strong evolution of the far-infrared luminosity function. The fainter 450- μ m sample has ∼14 times higher space density than the brighter 850- μ m sample at z ≲ 2, and a comparable space density at z = 2–3, before rapidly declining, suggesting LIRGs are the main obscured population at z ∼ 1–2, while ULIRGs dominate at higher redshifts. We construct rest-frame ∼180- μ m-selected and dust-mass-matched samples at z = 1–2 and z = 3–4 from the 450 and 850- μ m samples, respectively, to probe the evolution of a uniform sample of galaxies spanning the cosmic noon era. Using far-infrared luminosity, dust masses, and an optically thick dust model, we suggest that higher redshift sources have higher dust densities due to inferred dust continuum sizes which are roughly half of those for the lower redshift population at a given dust mass, leading to higher dust attenuation. We track the evolution in the cosmic dust mass density and suggest that the dust content of galaxies is governed by a combination of both the variation of gas content and dust destruction time-scale.